Large inversion effects for common objects and objects that require little if any holistic processing - Christian Gerlach (Scientific Reports, 2025)
Abstract It is widely assumed that faces are processed holistically whereas objects are not because only face recognition efficiency is greatly affected when stimuli are presented upside-down. This phenomenon – the face inversion effect – has been taken as support for both theories of domain-specificity and expertise, and as an index of holistic/configural processing. The present study, which comprised 122 Danish psychology students, demonstrates that large inversion effects can be found for objects too, even when they do not belong to categories of expertise or are structurally similar. Furthermore, inversion effects were also found in conditions that require little if any holistic processing. While these findings do not refute that face processing may be domain-specific, a product of expertise, or that inversion effects can reflect holistic/configural processing, they do suggest that inversion effects by themselves provide little specific evidence in favor of any these assumptions.